The Influence of Social Media Marketing and Customer Reviews on Nanailart Customer Satisfaction in Bandar Lampung - Purnamasari, Wayan; Patmarina, Hepiana (Eastasouth Institute, 2025)
This study aims to determine the effect of Social Media Marketing and Customer Review on Customer Satisfaction of Nanailart in Bandar Lampung. The research method used is quantitative descriptive, with questionnaire data collection and documentation to fulfill collective data. The analysis technique used is multiple linear regression test and coefficient of determination to answer the formulated hypothesis. Based on the results of the analysis, it is concluded that social media marketing and customer review have a positive effect on customer satisfaction of nanailart on Instagram, with a regression coefficient value of R = 0.748 indicating a significant correlation between predictor variables and customer satisfaction. R Square of 0.780 means that around 78% of customer satisfaction variability can be influenced by social media marketing and customer review variables. Positive customer reviews provide social proof that validates the quality of a product or service, while social media marketing allows brands to interact directly with customers, building closer and more responsive relationships. These two factors work together to create better expectations, strengthen loyalty, and increase overall customer satisfaction.